Budgets for Pasture Establishment: Seeded and Vegetative - Les Harrison; Jonael Bosques; Yoana Newman (EDIS, 2014)
Budgets can be used to make rational decisions when establishing or renovating a pasture in Florida. This 3-page fact sheet is a guide for evaluating the costs of establishing a seeded-type pasture versus vegetatively propagated hybrid bermudagrasses. Written by Les Harrison, Jonael Bosques, and Yoana Newman, and published by the UF Department of Agronomy, August 2014.